Safety, health improvement and well-being during a 4 to 21-day fasting period in an observational study including 1422 subjects - Wilhelmi de Toledo, Françoise; Grundler, Franziska; Bergouignan, Audrey; Drinda, Stefan; Michalsen, Andreas (PloS one, 2019)
Only few studies document longer periods of fasting in large cohorts including non-obese participants. The aim of this study was to document prospectively the safety and any changes in basic health and well-being indicators during Buchinger periodic fasting within a specialised clinic. In a one-year observational study 1422 subjects participated in a fasting program consisting of fasting periods of between 4 and 21 days. Subjects were grouped in fasting period lengths of 5, 10, 15 and 20±2 days. The participants fasted according to the Buchinger guidelines with a daily caloric intake of 200-250 kcal accompanied by a moderate-intensity lifestyle program. Clinical parameters as well as adverse effects and well-being were documented daily. Blood examinations before and at the end of the fasting period complemented the pre-post analysis using mixed-effects linear models. Significant reductions in weight, abdominal circumference and blood pressure were observed in the whole group (each p<0.001). A beneficial modulating effect of fasting on blood lipids, glucoregulation and further general health-related blood parameters was shown. In all groups, fasting led to a decrease in blood glucose levels to low norm range and to an increase in ketone bodies levels (each p<0.001), documenting the metabolic switch. An increase in physical and emotional well-being (each p<0.001) and an absence of hunger feeling in 93.2% of the subjects supported the feasibility of prolonged fasting. Among the 404 subjects with pre-existing health-complaints, 341 (84.4%) reported an improvement. Adverse effects were reported in less than 1% of the participants. The results from 1422 subjects showed for the first time that Buchinger periodic fasting lasting from 4 to 21 days is safe and well tolerated. It led to enhancement of emotional and physical well-being and improvements in relevant cardiovascular and general risk factors, as well as subjective health complaints.